Ngoni - Language, Culture and Sociolinguistic Situation - Photo Elicitation Traditional Objects - Rosendal, Tove; Mapunda, Gastor (University of Gothenburg, 2014)
The project comprised three interrelated parts: A main project Language documentation and analysis of Ngoni, which was a joint project by Tove Rosendal and Gastor Mapunda, and two subprojects: The Ngoni culture - a documentation project (Gastor Mapunda), and Language vitality and intergenerational transmission of the language Ngoni - a sociolinguistic survey (Tove Rosendal).

The archived data are from the project part Language documentation and analysis of Ngoni. It consists of a set of recordings from elicitations using photos depicting local community situations (agriculture i.e. a farming scene, kitchen, i.e. an outdoor cooking scene and 'modern items'), and a set of recordings based on photos of old, traditional items. In both sets of recordings the informants were encouraged to talk rather freely in Ngoni about the concepts in the photos and how these items are used, after a short introduction in Ngoni by a native speaker. Code-switching with Swahili was found in all recordings, but to a varying degree.

The transcriptions of the recordings are filed here, in addition to some photos of informants in an elicitation situation. Swahili spelling conventions are used for the transcriptions. Additionally, you will find a map indicating the villages where the recordings were made.

The recordings were conducted in the Songea Rural District, east of Lake Nyasa in the Ruvuma Region in southwestern Tanzania in November-December 2012 and in August-September 2013, in the Songea Rural District which is situated in the geographically middle of the Ngoni speaking area. In addition, some recordings were made in Michungwani in Tanga District in September 2013.
The data recorded in Songea District were collected in linguistically and socio-economically different contexts, in the villages Peramiho, Mhepai and Kilagano. Peramiho is a semi-urban centre, situated 24 kilometers northwest of Songea town. The area is also home to German Benedictine Catholic missionaries who settled in the area more than 130 years ago. In Peramiho there is a big hospital, a church, banks, a police station, a printing press and artisan workshops. The people in the area are involved in activities ranging from formal employment, farming and petty businesses. People who live in Peramiho are relatively more educated than people from other locations around the district. Mhepai is a small village 33 km further northwest of Peramiho, 62 kilometres from Songea town. The place is remote with only one primary school. Additionally, due to the nature of the place, interaction with the rest of the Songea Region and also the rest of Tanzania is limited. Only recently a mini-bus started to ply the route, and only once a day. The introduction of Chinese motorbikes has recently made the village a bit more accessible. Exposure to mass media is very limited due to lack of electricity. Most people in the place are small scale farmers, and are also involved in small scale animal husbandry and poultry, basically for domestic consumption.
Kilagano is another small and isolated village in the same area, northwest of Songea. The living conditions are similar to the conditions in Mhepai.
The data also consist of recordings of old people who moved away from the Ngoni speaking area around 1950 to work on sisal plantations in Michungwani in the Tanga region of Tanzania.
The recordings of photo elicitations of agriculture (farming scene), kitchen (outdoor cooking scene) and 'modern items' were made by 12 informants in Peramiho, 12 in Mhepai and 4 in Michungwani, Tanga region.
Recordings of descriptions of old items were made by 7 informants in Peramiho, 6 in Kilagano and 4 in Michungwani, Tanga region.

The informants were from three age groups: 15-30 years, 31-50 years and 51 years or older (age varied between 57 and 94 years). 50 % of the informants were men and 50 female, see metadata information attached as an Excel file ("Documentation" tab above).

Purpose:

The project "Ngoni - Language, culture and sociolinguistic situation" as a whole is a contribution to safeguarding the Ngoni culture, by documenting, preserving and analysing its intangible cultural heritage. Its focus was especially on language, both as a resource for indigenous knowledge and as a socio-linguistic indicator of cultural vitality in a contact situation with Swahili. The aim of the analysis of the elicitated recordings was to investigate the influence of Swahili which has been promoted for decades and today is spoken all over Tanzania. Simultaneously the project aimed at documenting other aspects of Ngoni culture. The archived data are from the project part Language documentation and analysis of Ngoni, which aimed at investigating how Ngoni is influenced by Swahili, especially focusing on borrowing and code-switching.

The dataset contains 17 recordings of elicitation sessions with photos of traditional objects. Along with the recordings the dataset comes with transcripts, the photos used in the elicitation and a metadata file.

Projektet ”Ngoni - Language, culture and sociolinguistic situation” är ett tvåårigt postdokprojekt från forskningsprogrammet TASENE som är ett samarbete mellan Tanzania (COSTECH), Sverige (SIDA) och Nederländerna (NWO, Netherlands Organisation for Scientific Research/WOTRO Science for Global Development).
Det arkiverade materialet kommer från delprojeketet Language documentation and analysis of Ngoni. Materialet består av ljudinspelningar (elicitering baserat på foton av situationer från den lokal miljön: jordbruk, matlagning över öppen eld samt vad som kan betecknas 'moderna föremål'). Det finns även inspelningar (även här elicitering genom foton) som visar gamla, traditionella föremål. Alla inspelningar är på ngoni, men kodväxling med swahili förekommer i varierande omfattning. Inspelingarna är gjorda i Songea Rural District, öster om Lake Nyasa i Ruvuma Region i sydvästra Tanzania i november-december 2012 och i augusti-september 2013, i Songea Rural District som geografiskt är mitt i ngonitalarnas område. I tillägg finns inspelningar gjorda i Michungwani i Tanga District i September 2013. Inspelningarna från Songea District är gjorda i 3 olika byar, Peramiho som är ett mindre ekonomiskt center 24 km nordväst om Songea, och i två små isolerade byar som ligger ca 33-40 km längre nordväst om Peramiho: Mhepai och Kilagano.
Totalt finns 45 inspelningar. Alla är transkriberade. Swahili-stavningskonventioner har använts.
Det finns även metadata om informanterna, som är hämtade från 3 olika ålderskategorier: 15-30 år, 31-50 år och äldre än 51 år (ålder varierade mellan 57 och 94 år). 50 % av informanterna var män och 50 kvinnor, se metadatainformation i Excelfil (fliken "Dokumentation" ovan).

Syfte:

Projektet "Ngoni - Language, culture and sociolinguistic situation" hade som övergripande mål att dokumentera och analysera språket ngoni samt dokumentera olika aspekter av ngonis kultur. Genom att analysera hur språket ngoni används och påverkas av swahili, kan man dra slutsatser om ngonis framtid - om språket hotas eller om ngonitalare bevarar sitt språk i kontaktsituationen med swahili. Swahili är det nationella språket som genom politiska beslut har utvecklats till att bli kommunikationsspråk över hela Tanzania. Det finns fog för att anta att swahili är ett hot mot många av Tanzanias minoritetsspråk, däribland ngoni. Syftet med filerna från delprojektet Language documentation and analysis of Ngoni var att analysera lån och språkväxling med swahili.

Datasetet innehåller 17 inspelningar av eliciteringssessioner med foton på traditionella föremål. Utöver inspelningarna medföljer också transkriptioner, fotona som användes i eliciteringen och en metadatafil.
Ngoni - Språk, kultur och sociolingvistisk situation - Fotoelicitering traditionella föremål
Keywords: endangered languages; hotade språk; code-switching; kodväxling; borrowing; lån; language documentation; språkdokumentation; language contact; språkkontakt; Ngoni; ngoni; Swahili; swahili; Language and linguistics; Språk och lingvistik; Sociology (Excluding Social Work, Social Anthropology, Demography and Criminology); Sociologi (exklusive socialt arbete, socialantropologi, demografi och kriminologi); Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik